2016
DOI: 10.1002/aelm.201600330
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Growth of MoS2 via Atomic Layer Deposition of Molybdenum Oxide Film Precursor

Abstract: The growth of atomically thin MoS2 films is achieved by sulfurization of molybdenum oxide precursor films grown by atomic layer deposition. The quality features of the MoS2 films are engineered controlling the stoichiometry, morphology, and thickness of the precursors. The interface interaction between the precursor films and the substrates (SiO2 or sapphire) plays a key role in the MoS2 formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 16 publications
2
50
0
Order By: Relevance
“…First, the as‐grown MoS 2 film was investigated by atomic force microscopy (AFM) (Figure a). It was found that the film is relatively smooth with an RMS value ≈ 0.5 nm, which is consistent with the previously reported data of 0.4, 0.8, and 0.2 nm . As shown in Figure a, the film revealed the sharp edge grain‐like structure with grain lateral sizes up to ≈ 200 nm.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…First, the as‐grown MoS 2 film was investigated by atomic force microscopy (AFM) (Figure a). It was found that the film is relatively smooth with an RMS value ≈ 0.5 nm, which is consistent with the previously reported data of 0.4, 0.8, and 0.2 nm . As shown in Figure a, the film revealed the sharp edge grain‐like structure with grain lateral sizes up to ≈ 200 nm.…”
supporting
confidence: 90%
“…The subsequent MoO 3 sulfurization process was carried out in a three‐zone tube furnace, HZS‐1200 (Carbolite Gero), equipped with a 32 mm outer diameter quartz tube. After loading the substrates, the tube was purged for 1 h to obtain Ar (99.9999%) atmosphere (150 sccm flow) at room temperature similar to the procedure described in previous studies . The sulfurization process was performed at 900 °C with elemental sulfur located upstream from the sample in a tube.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is necessary to develop methods to engineer the structural, excitonic, and electronic properties of 2D ML chalcogenide without compromising continuity and homogeneity. The present report details a two‐step growth process that is based on a sulfurization process of molybdenum (Mo)‐containing (Mo metal, oxides, or compounds) precursor films at an elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…These methods can improve the uniformity of the process and resulted in successful large‐scale synthesis (Figure c). Atomic‐layer deposition (ALD) techniques have recently been used to deposit uniform MoO 3 film, which was converted into centimeter‐scale uniform MoS 2 films by reacting with sulfur in a later process . Usually the controllability in terms of layer numbers is not great, and the grain size is very small (tens of nanometers) in the as‐synthesized films, which limits the use of such 2D films for high‐performance electronic applications due to the existence of a large number of grain boundaries.…”
Section: Preparation Of 2d Semiconductorsmentioning
confidence: 99%